Dynamique De La Mangrove De Thiobon Dans L’estuaire De La Casamance (Sénégal) Entre 1972 Et 2017 - Solly, Boubacar; Dièye, El Hadji Balla; Sané, Tidiane; Diaw, Amadou Tahirou (European Scientific Journal, ESJ, 2018)
In the village soil of Thiobon in lower Casamance (southern Senegal), site being established as Marine Protected Area (MPA), the main activities of the population (rice growing, harvesting of fish products, salt production, …), happens in mangrove zone. These mobilize the population for several months in the year. This mangrove ecosystem, vulnerable and fragile, has undergone profound changes since the 1960s under the combined actions of rainfull variability and main. This study proposes to analyze the spatio-temporal dynamics of Thiobon mangrove. The method used is based on the processing and analysis of satellite data (Landsat imagery acquired in 1972, 1986, 2000 and 2017), rainfall data (1960 to 2017), and on the perception of populations of change in their terroir (field investigation). Map results indicate an overall decline on 52% in mangrove area in tanne during drought years (1970 to the late 1990s). During 2000–2017, characterized by the almost normal return of the rainfall and activities of reforestation done by the local population, about 69% of the mangrove areas lost between 1972 and 2000 regenerated. This dynamic is the result of external and internal forces exerted on this ecosystem and evolve since the early 1970s.